Metabolism of Zearalenone by Genetically Modified Organisms Expressing the Detoxification Gene from Clonostachys rosea - Takahashi-Ando, Naoko (American Society for Microbiology, 2004)
Zearalenone (ZEN) is converted to a nontoxic product by a lactonohydololase encoded by zhd101. An enhanced green fluorescent protein (EGFP) gene was fused to zhd101 (i.e., egfp::zhd101) and expressed in Escherichia coli. Both recombinant ZHD101 and EGFP::ZHD101 were purified to homogeneity and characterized. Maximal activity of ZHD101 toward ZEN was measured at approximately 37 to 45°C and pH 10.5 (k(cat) at 30°C, 0.51 s(−1)). The enzyme was irreversibly inactivated at pH values below 4.5 or by treatment with serine protease inhibitors. ZHD101 was also active against five ZEN cognates, although the efficiencies were generally low; e.g., the k(cat) was highest with zearalanone (1.5 s(−1)) and lowest with β-zearalenol (0.075 s(−1)). EGFP::ZHD101 had properties similar to those of the individual proteins with regard to the EGFP fluorescence and lactonohydrolase activity. Fortuitously, EGFP::ZHD101 exhibited a good correlation between the fluorescence intensity and reaction velocity under various pH conditions. We therefore used egfp::zhd101 to visually monitor the lactonohydrolase activity in genetically modified organisms and evaluated the usefulness of zhd101 for in vivo detoxification of ZEN. While recombinant E. coli and transgenic rice calluses exhibited strong EGFP fluorescence and completely degraded ZEN in liquid media, recombinant Saccharomyces cerevisiae gave poor fluorescence and did not eliminate all the toxicity of the mycotoxin in the medium; i.e., the rest of ZEN was transformed into an unfavorable substrate, β-zearalenol, by an as-yet-unidentified reductase and remained in the medium. Even so, as much as 75% of ZEN was detoxified by the yeast transformant, which is better than the detoxification system in which food-grade Lactobacillus strains are used (H. El-Nezami, N. Polychronaki, S. Salminen, and H. Mykkuäne, Appl. Environ. Microbiol. 68:3545-3549, 2002). An appropriate combination of a candidate host microbe and the codon-optimized synthetic gene may contribute significantly to establishing a mycotoxin detoxification system for food and feed.